Rapid hardening of electrospun foam in water for minimally invasive surgery - Dinesh S/O Chandran (Nanyang Technological University, 2023)
Thermoplastic polyurethane is a non-toxic material that is suitable for medical application. By the process of electrospinning, we are able to produce a membrane due to its shape memory effect (SME). In this study, we are interested in using TPU for potential medical applications. One such application would be in removing blood clots in blood vessels. To achieve this, the TPU membrane would require curling and crumpling capabilities when exposed to a stimulus. Therefore, is it crucial to achieve this effect. Attempts have been made by previous individuals to assess TPU Samples of the shrinkage effect and physical changes of the sample when exposed to a certain stimulus. In this report we explore the fabrication of the 3D structure creation of the TPU Samples. With the development in nanotechnology, this material has the potential to be used in intricate medical applications and make a positive impact in the medical industry.